2004
DOI: 10.1242/dev.01253
|View full text |Cite
|
Sign up to set email alerts
|

Parallels between tissue repair and embryo morphogenesis

Abstract: Review 3022tissue movements as in the adult, although on a much smaller scale, but only at late foetal stages is healing accompanied by an inflammatory response (Hopkinson-Woolley et al., 1994; Cowin et al., 1998). Prior to these stages, inflammation is absent and the embryo is capable of essentially perfect, near regenerative repair, with no resulting scar. Wound healing, even in the embryo (Fig. 2), is a complex process involving the coordination of several cell behaviours from several different cell types,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
405
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 517 publications
(424 citation statements)
references
References 128 publications
11
405
2
Order By: Relevance
“…3A,B), indicating a regional heterogeneity of the eyelid anlagen by this stage or a functional difference of these two receptors in eyelid development. As reported previously, epithelial proliferation and subsequent migration leads to eyelid development (Martin and Parkhurst, 2004;Tao et al, 2005). Our findings suggest that LPA/S1P lipids might regulate epithelial migration in mouse eyelid development by binding to LPA 1 and S1P 1-3 receptors.…”
Section: Potential Roles For Multiple Lpa/s1p Receptor Subtypes Durinsupporting
confidence: 85%
“…3A,B), indicating a regional heterogeneity of the eyelid anlagen by this stage or a functional difference of these two receptors in eyelid development. As reported previously, epithelial proliferation and subsequent migration leads to eyelid development (Martin and Parkhurst, 2004;Tao et al, 2005). Our findings suggest that LPA/S1P lipids might regulate epithelial migration in mouse eyelid development by binding to LPA 1 and S1P 1-3 receptors.…”
Section: Potential Roles For Multiple Lpa/s1p Receptor Subtypes Durinsupporting
confidence: 85%
“…Such similarity in tissue repair in stroke to neurodevelopment has prompted suggestions that brain regeneration recapitulates development 117. Similar comparisons to regeneration and development have been made in other systems, such as kidney, bone, liver, and skin 118, 119, 120, 121…”
Section: Regeneration Does Not Recapitulate Developmentmentioning
confidence: 81%
“…Finally, that Xenopus embryos manage to seal furrows under a variety of experimental conditions, including expansion or removal of the vitelline envelope, indicates a robust and responsive system, presumably using redundant interacting regulatory pathways, and, therefore, reflecting the developmental importance of furrow closure. In this report, we examined two dynamic activities of furrow closure that are commonly encountered in other epithelial sheet fusions, namely the development of an actin-dependent purse-string constriction along free apical-basolateral margins, and a margin-associated protrusive activity (Martin and Parkhurst, 2004). Additionally, we found that the basolateral domains autonomously produce active protrusive zones that act across large surface areas to bring bare adhesive membranes into contact.…”
Section: Discussionmentioning
confidence: 96%
“…Zippering by the first cleavage furrow closes a 1-mm opening in approximately 15 min. While wound closure in tissue culture models (Farooqui and Fenteany, 2004) or Drosophila dorsal closure (Martin and Parkhurst, 2004) typically involves participation by hundreds of cells in multiple rows, Xenopus firstfurrow closure involves the suturing of apical-basolateral margins between only two blastomeres. Epithelial wound-healing models are essentially 2D, whereas Xenopus cleavage is 3D, with interactions between both the basolateral domains and the apical margins contributing to the closure process.…”
Section: Discussionmentioning
confidence: 99%